Terms-of-trade and the funding of adaptation to climate change and variability: An empirical analysis - Oliver Schenker; Gunter Stephan (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper analyses the interplay between international trade, regional adaptation and North-to-South transfers for funding adaptation within the framework of a dynamic computable gen-eral equilibrium model, where impacts of climate change depend on changes in precipitation and temperature. If all regions, even the least developed ones, own the necessary resources for adapting optimally to climate change and variability, by mid-century less than 10% of the regions' GDP would be invested for avoiding almost 40% of climate change damages. This has measurable effects on the regions' competitiveness as well as on the terms-of-trade. If, however, the developing world does not own sufficient resources for adapting optimally to climate change, as is to expected, funding of adaptation can make sense from an economic perspective. In particular the Hicks-Kaldor criterion is fulfilled as aggregated welfare gains at least compensate the costs of providing financial assistance for adaptation.
Keywords: C68; D58; F18; Q56; Q54; 330; funding of adaptation; climate change; international trade; multi-regional dynamic CGE model